Comparative study of male and female human hair: A microscopic analysis - S Sneha Harshini; Vishnu Priya Veeraraghavan; Abirami Arthanari; R Gayathri; S Kavitha; J Selvaraj; P K Reshma; Y Dinesh (Wolters Kluwer Medknow Publications, 2022)
The outer cuticle, middle cortex, and inner medulla make up hair, which is an epidermal outgrowth. Hair is resilient under harsh natural conditions, thus it is frequently collected at crime scenes, making human hair analysis important in the forensic sciences field. It aids in the formation of a triangle connecting a crime scene, a victim, and a culprit. The aim of this study is to observe the microscopic structure of male and female human hair. Samples of hair specimens from males and females were collected. The materials used were ethanol to degrease and a stereomicroscope to observe the structural differences between the male and female hair samples. The comparison between male and female hair is done on the grounds of color, shaft profiles, the proximal and distal ends of the hair, cuticle, and surface texture, and the other found characters. This study of comparison between male and female hair specimens revealed that the hair color at the distal end is found to be brown for females while it is completely black in that of males, and the surface texture of males is found to have some irregularities while there are no irregularities in female. This study can be concluded that the structural comparison between male and female hair specimens can be used as evidence for forensic analysis at crime scenes.